MOORE–PENROSE INVERSE OF BIDIAGONAL MATRICES. II - Hakopian, Yu.R.; Aleksanyan, S.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
The present paper is a direct continuation of the paper [1]. Here we start our study of the Moore–Penrose inversion problem for upper bidiagonal matrices with any arrangement of one or more zeros on the main diagonal. In the paper we obtain some preliminary results, which will be used in subsequent, third part of the study.